High-Density Genomic Characterization of Native Croatian Sheep Breeds - Drzaic, Ivana; Curik, Ino; Lukic, Boris; Shihabi, Mario; Li, Meng-Hua; Kantanen, Juha; Mastrangelo, Salvatore; Ciani, Elena; Lenstra, Johannes A.; Cubric-Curik, Vlatka (Frontiers Research Foundation, 2022)
A recent comprehensive genomic analysis based on 50K SNP profiles has shown that the regional Balkan sheep populations have considerable genetic overlap but are distinctly different from surrounding breeds. All eight Croatian sheep breeds were represented by a small number of individuals per breed. Here, we genotyped 220 individuals representing the native Croatian sheep breeds (Istrian Sheep, Krk Island Sheep, Cres Island Sheep, Rab Island Sheep, Lika Pramenka, Pag Island Sheep, Dalmatian Pramenka, Dubrovnik Sheep) and mouflon using the Ovine Infinium® HD SNP BeadChip (606,006 SNPs). In addition, we included publicly available Balkan Pramenka and other Mediterranean sheep breeds. Our analyses revealed the complex population structure of Croatian sheep breeds and their origin and geographic barriers (island versus mainland). Migration patterns confirmed the historical establishment of breeds and the pathways of gene flow. Inbreeding coefficients (FROH>2 Mb) between sheep populations ranged from 0.025 to 0.070, with lower inbreeding coefficients observed in Dalmatian Pramenka and Pag Island Sheep and higher inbreeding in Dubrovnik sheep. The estimated effective population size ranged from 61 to 1039 for Krk Island Sheep and Dalmatian Pramenka, respectively. Higher inbreeding levels and lower effective population size indicate the need for improved conservation management to maintain genetic diversity in some breeds. Our results will contribute to breeding and conservation strategies of native Croatian sheep breeds.
Keywords: sheep; genome; SNP; genetic resources; genetic variation; breed; adaptation; Croatian sheep breeds; effective population size; genomic characterization; inbreeding; population structure